Lower Gondwana megaflora, palynoflora, and biomarkers from Jagannath Colliery, Talcher Basin, Odisha, India, and its biostratigraphic significance. Issue 3 (17th November 2021) - Patel, Roshni; Goswami, Shreerup; Aggarwal, Neha; Mathews, Runcie Paul
Abstract : The study of megafossils, palynomorphs, and biomarkers has been carried out from a fossiliferous section of Jagannath Colliery, Talcher Basin, Odisha, India. The megafloral assemblage recovered from the carbonaceous shale bed of the investigated section comprises 15 Glossopteris species (leaf form), Vertebraria indica (root form), and stem cast of the order Glossopteridales. The megafloral assemblage and lithology (grey shale, carbonaceous shale, sandy shale, and coal seams) of the litho‐column suggest that the sediments belong to the Barakar Formation (Artinskian‐Kungurian age). Palynoflora recovered from the section is dominated by Striatopodocarpites spp. (35–44%) and subdominated by Faunipollenites spp. (29–35%) along with a good percentage of Densipollenites spp. Stratigraphically significant taxa of this palynoassemblage show its affinity toward the late Permian (Wuchiapingian‐Changhsingian) palynoflora which is geologically mapped as Barakar Formation of early Permian (Artinskian‐Kungurian) age. As a result, to clearly delimit the distribution of different lower Gondwana strata in this area, more precise palynological sampling and extensive geological mapping should be undertaken. The dominant occurrence of short‐chain n ‐alkanes in the samples suggests the abundance of algal and microbial sources that are deposited in moderate water level conditions in the basin. Pristane/phytane ratio suggests oxic settings while the hopane distribution in the studied samples suggests significant bacterial degradation of the peat biomass in the depositional milieu. Abstract : The present study is an all‐encompassing original research work on the megafossils, palynoflora, and biomarkers of the Jagannath Colliery, Talcher Basin, Odisha, India. These three proxies have been explored for a better understanding of palaeoclimate, palaeoenvironment, palaeoecology, and source vegetation.